Autopsy findings in severe malaria - a case report (Faculty of Medicine Universitas Indonesia, 2008)
Severe malaria, caused by Plasmodium falciparum infection, has a high mortality rate and is the main cause of death in malaria. Since clinical autopsy is unpopular in Indonesia, autopsy examination in malaria cases is rarely done. We reported a forty three year old woman from non endemic area that was dead because of severe malaria. Diagnosis was concluded from autopsy, histopathology, and toxicology. (Med J Indones 2008; 17: 210-5)